Implementasi Manajemen Peningkatan Mutu Pendidikan di Kabupaten Brebes - Suwarjono Suwarjono (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
The rationale of this research are based on the quality of the school and the quality of the graduates is still low, the implementation of sentaralistic education, the school management is not appropriate, the input-output analysis approach, the participation of the community is still weak, and cooperation is still low. Research objectives are: (1) to describe how the implementation of MPMBS in Brebes Regency is seen from the planning, implementation, and evaluation; (2) to describe what factors support and inhibit the implementation of school-based management in Brebes district primary schools; (3) to formulate the implementation model of MPMBS in Brebes District. This research method is descriptive and using qualitative approach. Data collection techniques: data collection methods using interviews, observation, documentation, and triangulation, while data analysis uses data reduction, display data and conclusion drawing. The qualitative research procedure is conducted through three stages are: (1) preparatory / orientation study, (2) general exploration study, and (3) focus exploration study. The results of the research are (1) MPMBS planning is arranged in accordance with the vision and mission of the school, but not yet based on the analysis of the need for quality improvement either from the academic aspect or the resources needed to support the realization of the school quality and the quality of the graduates. (2) Implementation of MPMBS in Brebes Regency has been implemented based on management functions but in implementation there is no adequate cost support. (3) Evaluation of MPMBS in Brebes Regency has been implemented, but has not used the correct evaluation technique. (4) Factors supporting the implementation of MPMBS in Brebes District include teachers, school committees, students, parents (wali murid). And the inhibiting factors of MPMBS implementation in Brebes primary school are human resources, parents (wali murid) and welfare. (5) Research recommendation are: School principals should not only be oriented towards the vision, mission and objectives of the school but should be based on needs analysis and for school committees to participate and enhance cooperation with various stakeholders related to quality improvement. (6) Formulation of MPMBS implementation model named "The Best Procces" model. This model aims to create high quality schools and graduates, namely schools that prioritize good planning, implementation, and evaluation processes, supported by management having characteristics that enhance students' cognitive, affective, psychomotoric, believing skills, and operational skills.